Electrocardiographic abnormalities and associated factors among HIV-infected adults on antiretroviral therapy - Befkadu, Zewudu; Ibrahim, Mohammed; Tadelle, Amanuel; Tegene, Elsah (Frontiers in Reproductive Health, 2024)
BackgroundIndividuals living with HIV are at increased risk of developing cardiovascular diseases. This heightened vulnerability is influenced by various factors, including the direct impact of HIV infection, the side effects of HIV medications, and a higher presence of traditional cardiovascular risk factors. Detecting and managing cardiovascular diseases early in HIV-infected individuals is crucial for their overall health and well-being. Electrocardiography, a simple and non-invasive test, can provide valuable information in this regard. However, there is currently no published data on the prevalence of electrocardiographic abnormalities and the associated factors among HIV-infected adults in Ethiopia.ObjectivesThis study was aimed at assessing the prevalence of ECG abnormalities and associated factors among HIV-infected adults on antiretroviral therapy.MethodologyA hospital-based comparative cross-sectional study was conducted at Mettu Karl Specialized Hospital (MKSH), southwest Ethiopia, among 96 HIV-infected patients and 96 HIV-negative control groups. A systematic random sampling technique was used to select HIV-infected respondents, and HIV-negative respondents were purposively recruited from caregivers. A face-to-face interview with a semi-structured and pretested questionnaire was conducted to collect the socio-demographic and behavioral characteristics of the study participants. Electrocardiography was done for all study participants using a 12-lead electrocardiograph, interpreted by a cardiologist, and classified according to the Minnesota Code classification system. The data were entered into Epi-Data version 4.6 and exported to SPSS version 25 for analysis. Finally, descriptive statistics, chi-square, independent t-test, bivariable, and multivariable logistic regression analyses were done at a 5% significance level.ResultsThe study found that 49% of HIV-infected and 19.8% of HIV-negative participants had at least one ECG abnormality. The proportion of coded ST-segment abnormalities, T-wave abnormalities, longer QT interval, and sinus tachycardia was significantly higher in HIV-infected respondents than in HIV-negatives. Being a smoker [AOR = 3.7, 95%CI: 1.03–13.6], being on Protease inhibitors [AOR = 3.6, 95%CI: 1.02–13.1] and having CD4 less than 350 cells/mm3 [AOR = 3.2, 95%CI: 1.22–8.49] were significantly associated with ECG abnormalities among HIV-infected respondents.ConclusionCompared to HIV-negative participants, HIV-infected patients had a significantly higher prevalence of ECG abnormalities. Screening for ECG abnormalities is needed for the early detection of cardiac abnormalities and the reduction of future complications.